Youth-Led Initiative in Re-Building Education in Crises Zone: Challenges and Innovation (A Case Study of Borno State, Nigeria) - Buhari, Hadiza; Sanda, Amina Abba; Sakir, Aishatu (NIU Journal of Humanities; Vol 10 No 4 (2025): NIU Journal of Humanities, Vol. 10 No. 4, December 2025, 2025)
The study examined Youth-led initiative in re-building education in crises zone: challenges and innovation. Three objectives guided the study. The study adopts a descriptive survey research design. The population of this study comprises youth leaders, volunteers, NGO staff, educators, and beneficiaries involved in youth-led education initiatives in Borno State. The population of the study is 350 youths. A sample size of 200 respondents was drawn from the target population using a purposive and stratified random sampling techniques. The instrument for Data Collection was questionnaire. Each item was measured using a five-point Likert scale, ranging from Strongly Agree (5) to Strongly Disagree (1). Data was collected using Kobo Collect, a digital data-gathering tool developed for field-based research in humanitarian and development settings. The questionnaire was designed and uploaded to the KoboToolbox server, which allowed respondents’ information to be collected efficiently using smartphones or tablets. The instrument was validated by experts in Adult and Non-Formal Education and Educational Research from the University of Maiduguri. Reliability coefficient of .849 was obtained for the instrument using Cronbach Alpha Coefficient method. Data collected was analyzed using descriptive statistics such as means and standard deviation was used to answer the research questions. Findings from the study shows that; Center for Advocacy, Transparency and Accountability Initiative (CATAI) plays an important role in rebuilding education and promoting youth participation in crisis-affected areas of Borno State. The organization enhances educational opportunities for vulnerable and displaced youths through literacy, skills training, and mentorship programs. Innovative approaches such as digital learning, community-based education, and psychosocial interventions are key strategies used by CATAI to sustain learning. Based on the findings of the study, the following recommendations were made; The Borno State Government and the Federal Ministry of Education should provide financial, logistis, and policy support to youth-led organizations like CATAI. CATAI should invest in continuous capacity development for its staff and volunteers in areas such as digital pedagogy, psychosocial care, monitoring and evaluation, and humanitarian education management to improve program delivery. Development partners, donor agencies, and private organizations should collaborate with CATAI to establish long-term funding mechanisms that ensure sustainability of youth-led education programs beyond short-term humanitarian cycles. Keywords: Youth-led, Initiative, Re-building, Education, Crises Zone, Challenges, Innovation